A quasi-experimental study on the color perception of individuals with dichromatism - Cortejos, Sarah Grace Z.; Mayo, Adelaida Villaraza (Quezon City College of Home Economics, University of the Philippines Diliman, 2010)
ABSTRACT This study, using a quasi-experiment that aimed to evaluate and analyze the color perception of individuals with dichromatism, a kind of color vision deficiency, was conducted to develop color schemes for interiors ideal for them. Using purposeful sampling, the selection of two groups of respondents was made based on the following criteria: 1) the first group consisted of four individuals with dichromatism; 2) the second group was composed of four individuals with normal color vision; and 3) all eight respondents belonged to the age range of 17 to 21 years old. Each of them was interviewed, and subjected to two tests, the first to validate their eye condition, and the second to assess their color perception. An ophthalmologist was also consulted for purposes of validation regarding the study. Data derived from the interviews and tests were analyzed based on the color wheel theory, corroboration from an expert on dichromatism, and materials on previous studies related to the subject. The results showed that three respondents with dichromatism did not pass the tests, while one dichromatic respondent passed. All four respondents with normal color vision passed the tests. Based on the test results and the interviews, it was concluded that the dichromatic respondents relied on the contrast between the different hues to be able to tell them apart. Coping mechanisms for dichromatic persons include using the colors found in nature as reference colors. However, dichromatic people may not perceive colors in the same way when compared with one another. It must be kept in mind that this study only had four dichromatic respondents, thus, their responses might not necessarily be similar for anyone else who has dichromatism. Therefore, selecting color schemes for them should be done on a case-to-case basis. It was recommended for future researchers to search for more respondents with dichromatism, so as to get more insights and perspectives on how dichromatic individuals deal with their condition.
Thesis (B.S. Interior Design)--University of the Philippines Diliman.
Keywords: Color vision